A phylogenetic analysis of the aquatic weevil tribe Bagoini (Coleoptera: Curculionidae) based on morphological characters of adults - Caldara, Roberto; O’brien, Charles W.; Meregalli, Massimo (Zootaxa, 2017)
Relationships of almost all known Bagoini from the world (Holarctic, Afrotropical and Oriental Regions, and Australia) were analyzed using morphological characters. To define relationships with other Curculionidae and among the species within the tribe, 119 characters were used: 64 of these are genital structures, mainly from the males, where the penis and endophallus are endowed with many complex structures that are apparently unique in Curculionidae. In general, the genital characters appear conservative and tend to resolve relationship at more terminal levels of phylogeny. On the contrary, many external characters are strongly homoplastic, probably secondary modifications associated with their aquatic lifestyle, but which tended to resolve relationships among the lower nodes of the tree. On the basis of this analysis, we confirmed the monophyly of the tribe. Our phylogenetic reconstruction suggests a new taxonomic ordering of the tribe in genera and subgenera. The following taxa, previously considered as synonyms of Bagous Germar, 1817, are resurrected as valid taxa: Hydronomus Schoenherr, 1825 and Memptorrhynchus Iablokoff-Khnzorian, 1960 as genera; Parabagous Schilsky, 1907, Hydronoplus Fairmaire, 1898 (= Pseudobagous Sharp, 1917 syn. n.) (stat. n.) and Macropelmus Dejean, 1821 (= Pnigodes LeConte, 1876 syn. n.) (stat. n.) as subgenera. Azollaebagous gen. n. and Hydrillaebagous subgen. n. of Bagous are created. Among some genera, especially Bagous and its subgenera, we recognize a somewhat large number of species groups, distinguishable mainly by unique character states of the male genitalia. Monophyly of most of these appears well supported. Some of these groups are presently monotypic, but we ascertained that many of them have other representatives not yet described.